2020
DOI: 10.3389/fmicb.2020.02037
|View full text |Cite
|
Sign up to set email alerts
|

VapC21 Toxin Contributes to Drug-Tolerance and Interacts With Non-cognate VapB32 Antitoxin in Mycobacterium tuberculosis

Abstract: The prokaryotic ubiquitous Toxin-antitoxin (TA) modules encodes for a stable toxin and an unstable antitoxin. VapBC subfamily is the most abundant Type II TA system in M. tuberculosis genome. However, the exact physiological role for most of these Type II TA systems are still unknown. Here, we have comprehensively characterized the VapBC21 TA locus from M. tuberculosis. The overexpression of VapC21 inhibited mycobacterial growth in a bacteriostatic manner and as expected, growth inhibition was abrogated upon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 94 publications
(147 reference statements)
1
43
0
Order By: Relevance
“…Notably, the VapBC TA family is the most abundant type of TA system encoded by Mtb (60). Several studies have demonstrated that host-mediated stress, such as hypoxia and activated macrophages, induces transcriptional activation of multiple VapBC TA loci (61)(62)(63). Hudock et al identified the transcriptional profile from granuloma samples of active and latent TB patients; the expression of eight dosR regulon members (Rv0080, Rv0081, Rv1736c, Rv1737c, Rv2032, Rv2625c, and Rv2630) along with the induction of four pairs of toxin/antitoxin (vapBC19, vapBC21, vapBC33, and vapBC34) were observed within the granulomas of active and latent TB patients (61).…”
Section: Toxin-antitoxin (Ta) Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, the VapBC TA family is the most abundant type of TA system encoded by Mtb (60). Several studies have demonstrated that host-mediated stress, such as hypoxia and activated macrophages, induces transcriptional activation of multiple VapBC TA loci (61)(62)(63). Hudock et al identified the transcriptional profile from granuloma samples of active and latent TB patients; the expression of eight dosR regulon members (Rv0080, Rv0081, Rv1736c, Rv1737c, Rv2032, Rv2625c, and Rv2630) along with the induction of four pairs of toxin/antitoxin (vapBC19, vapBC21, vapBC33, and vapBC34) were observed within the granulomas of active and latent TB patients (61).…”
Section: Toxin-antitoxin (Ta) Systemmentioning
confidence: 99%
“…Hudock et al identified the transcriptional profile from granuloma samples of active and latent TB patients; the expression of eight dosR regulon members (Rv0080, Rv0081, Rv1736c, Rv1737c, Rv2032, Rv2625c, and Rv2630) along with the induction of four pairs of toxin/antitoxin (vapBC19, vapBC21, vapBC33, and vapBC34) were observed within the granulomas of active and latent TB patients (61). Sharma et al demonstrated that VapC21 overexpression hinders mycobacterial growth, and co-expression of antitoxin VapB21 reverses this effect (62). Moreover, VapC21 overexpression mutant and Mtb cultured in stress conditions, such as nutrient deprivation and hypoxia, exhibited similar transcriptional profiles (62).…”
Section: Toxin-antitoxin (Ta) Systemmentioning
confidence: 99%
See 3 more Smart Citations